Moral intelligence in nursing: An evolutionary concept analysis - Zahra Hadian Shirazi; Raheleh Sabetsarvestani (Tehran University of Medical Sciences, 2021)
Background & Aim: Moral intelligence is a foundation and cornerstone of ethics in nursing. However, it is a vague concept which needs to develop. So, this study aimed to analyze the concept of moral intelligence in nursing to help its development and apply it in the context. Methods & Materials: Rodgers's evolutionary concept analysis method was used. Databases of Google Scholar, Science Direct, PubMed/Medline, Scopus, CINAHL, and IranMedex were searched from 2001 to 2020 with moral, ethics, intelligence, and nursing keywords. After considering the inclusion and exclusion criteria and removing irrelevant and duplicate articles, 46 texts were reviewed. The method of analysis was inductive content analysis. Results: The attributes of moral intelligence were identified as considering "individual-social value", "the integrity of feeling, thinking, and action", and "semantic purposefulness". The antecedents included "prepared person", "purposeful selection and upbringing", and "supportive context", and the consequences were "personal and professional development of the nurse", "facilitating holistic care", and "organizational promotion". Based on the attributes of the concept, moral intelligence was defined as: "The cognitive and value-oriented capability of a nurse in managing the problem and conflict resolution process through self-sacrifice and conscious involvement into intra-and-interpersonal relationships to achieve desirable moral and spiritual goals during comprehensive care of the client." Conclusion: In ethical challenges, moral intelligence may function as a cognitive ability by considering individual-social values. It uses a purposeful problem-solving process that is purposeful, seeks meaning, and guides nurses to improve the quality of health services.